Navigating research and publishing trends at Jinka University: Insights from Ethiopia - GoaYotta, E. (South African Journal of Higher Education, 2026)
This study explores the current trends in research and academic publishing at Jinka University, Ethiopia. The objectives include assessing the university’s research practices, examining the status of academic publications, and identifying factors influencing research and publication activities. A descriptive survey research design employing mixed methods was utilized, with data collected both quantitatively and qualitatively. Findings reveal that while Jinka University allocates sufficient research budgets and conducts periodic research review workshops, there is room for improvement in adherence to research guidelines, peer-reviewed proposal evaluations, and the provision of adequate research facilities. Academic publishing trends were found to be influenced by factors such as limited financial support, lack of incentives, insufficient training on predatory journals, and restricted access to reputable journals. Researchers also highlighted the importance of addressing attrition of experienced staff, enhancing research skills, and streamlining financial processes. The study underscores the need for improved research management, targeted training, and stronger institutional support systems to enhance research productivity and academic publishing outcomes at Jinka University.